Medical staff services quality to patients satisfaction based on SERVQUAL dimensions - Febri Endra Budi Setyawan; Stefanus Supriyanto; Feny Tunjungsari; Wa Ode Nurlaily Hanifaty; Retno Lestari (International Journal of Public Health Science (IJPHS), 2019)
Hospital service quality was a degree of discrepancy between patients’ perceptions and their expectations about hospitals services. Service quality which was provided by medical staff emphasizes the actual hospital service process.  In the hospital, patients’ satisfaction could be widely used to determine hospital service quality. The purpose of this study was to analyze the influence of medical staff services quality on patients satisfaction based on SERVQUAL dimensions. This study used an analytic observational design with cross-sectional approach. There were 314 respondents taken from inpatients hospital admission using simple random sampling. Based on regression analysis results, five dimensions of health services quality affect patients’ level of satisfaction and obtained the equation of Y = 0.026 + 0.226X1 + 0.332X2 + 0.1X3 + 0.075X4 + 0.235X5, this explained  that patients’ satisfaction was affected by all dimensions of health service quality (RATER) simultaneously. However, different values will be obtained if all dimensions were measured separately, range from 10% to 33.2%.  It could be concluded that patients’ satisfaction were influenced by the quality of medical staff services through its five components: reliability, assurance, tangible, empathy and responsiveness.